PENENTUAN KOEFISIEN TRANSFER MASSA PADAT CAIR PADA SISTEM TAWAS AIR DENGAN VARIASI KECEPATAN PUTARAN DAN DIAMETER PENGADUK - Ani Purwanti; Muhammad Yusuf; Wisnu Prayogo; Uli Anita Ambarita (KURVATEK, 2022)
Solid-liquid mass transfer data is very necessary for the design of mass transfer equipment, in which the coefficient determination is influenced by the rotation speed and diameter of the stirrer. Thus, this study aims to investigate the effect of variations in stirring speed and stirrer diameter on the mass transfer coefficient of a solid-liquid system. This research was conducted in a stainlesssteel stirred vessel with a diameter of 5 – 19.5 cm and a height of 20 cm equipped with baffles. The alum used was sized to pass a 20mesh sieve and retained by a 30mesh sieve. Alum was then put into a vessel with water as a solvent and stirred with stirring speed varies from 100-500 rpm. Every 10 seconds, 5 ml of sample was taken to analyze the concentration of alum by measuring its density. This experiment was carried out with variations in the speed of the stirrer rotation and the diameter of the stirrer with a constant D/Dt ratio. The result showed that there is a relationship between the mass transfer coefficient with the variables studied for the alum-water granular system in a stirred tank. The calculation results show an average deviation error of 0.66%. The dimensionless equation can be used to accurately evaluate the mass transfer coefficient experiment.